RESPON POSITIF MASYARAKAT AHLUSSUNAH WAL-JAMA’AH TERHADAP PANDEMI COVID-19 MENURUT MAQOSHID SYARI’AH - Rahman, Izza Amalia; Arini, Mercy Aprilia Dyah (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2021)
The outbreak of Corona Virus Disease or known as COVID-19, appeared for first time in China, precisely in Wuhan at the end of 2019. This virus then quickly spread to some countries in this world including Indonesia so it is referred to as a pandemic virus. Additionally, COVID-19 has also become a terror for almost all of communities because of its enormous impact in economic, educational, social and even religious aspects. This article is intended to observe about validity of the COVID-19 issues that has been going around among communities against Maqoshid Syari'ah, especially in the community of Pojok village in Blitar Regency. This study applies a qualitative descriptive research method by verifying the data through 3 approaches, namely the data approach, researcher perspective, and theoretical approach. The result indicates that the communities’ belief of the COVID-19 issues validation was based on phenomenon evidence and clarification carried out by the community. By believing the validity of these COVID-19 issues, the community has implemented the shari'ah which is by avoiding (Hifdzudnnafsi) themselves from the dangers of COVID-19. Therefore, the communities of Pojok Village have already implemented dharuhiyyat as an effort to protect the ummah and also apply certain prayers such as sholawat Tibbil Qulub and Li Khomsatun sholawat to seek protection to Allah SWT.